Kondisi Sosial Ekonomi Buruh Keluarga Pengrajin Batu Bata - Gietha Putri Aroem; Tubagus Hasanuddin (Politeknik Kesejahteraan Sosial Bandung, 2021)
Limited employment opportunities encourage people to look for other alternatives to find income to meet their family's needs. One of these alternatives is to become a brick production worker. The purpose of this study was to determine the socio-economic conditions of brick craftsmen workers’family. The research was conducted in Campang Raya Village, Sukabumi District, Bandar Lampung City from November to December 2019. The respondents were 15 people who were brick craftsmen who were determined purposively. Data analysis was performed by qualitative descriptive analysis. The results showed that the masonry workers were of productive age (100%), most of them (67%) had a low level of education. Average net income of IDR 3,320,000 - IDR 3,433,000 per month with a monthly per capita income of 1,106,000, - −Rp 1,147,000, - not meeting the UMR standard of Bandar Lampung City of IDR 2,445 .141, - Family brick craftsmen still do not get good housing facilities in the form of unsuitable housing, poor road facilities to the dwelling, and water sources that are difficult to obtain. The health facilities used for treatment is the puskesmas, the families of brick craftsmen workers do not have health insurance.